The Rhythm of Life: Lived Experiences of Asthmatic Individuals during the COVID-19 Pandemic (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2024)
The COVID-19 pandemic has had a profound impact on individuals worldwide, particularly those with pre-existing health conditions such as asthma. This study delves into the lived experiences of asthmatic individuals during the pandemic, shedding light on their unique challenges and resilience in the face of adversity. By employing the Husserlian Phenomenology method, researchers aimed to uncover the essence of these individuals' experiences, providing valuable insights into their struggles and triumphs. To ensure the safety and well-being of participants, strict adherence to COVID-19 protocols was maintained during face-to-face interviews. Through unstructured interviews, participants shared their narratives, offering a glimpse into the complexities of navigating life with asthma amidst a global health crisis. The central question guiding this study, "What are your experiences as an asthmatic individual during the COVID-19 pandemic?"-served as a compass for exploring the multifaceted dimensions of their journey. Using Colaizzi's method, data analysis revealed three overarching themes: Hardship Sonata, Melodic Contour, and Getting on Ballad. These themes encapsulate the participants' struggles, resilience, and adaptability in the face of unprecedented challenges. The metaphorical expression of the "Rhythm of Life" resonates deeply with their experiences, highlighting the ebb and flow of adversity and triumph that define their daily existence. Despite facing numerous obstacles, asthmatic individuals showcased remarkable courage, patience, and perseverance throughout the pandemic. Their narratives reflect a profound appreciation for life's beauty and a steadfast determination to overcome obstacles. The study underscores the resilience and strength exhibited by these individuals, emphasizing the importance of readiness to confront adversity and embrace life's uncertainties with unwavering resolve.
Keywords: Lived experiences; Asthmatic individuals; COVID-19